PERFORMA PRODUKSI ENTOG (Cairina moschata) JANTAN YANG DIBERI RANSUM BERBASIS HIJAUAN ECENG GONDOK (Eichhornia crasipess) - Nida Fitria; Dini Widianingrum; Rachmat Somanjaya (Tropical Livestock Science Journal, 2022)
The performance of mutton is influenced by quality feed, easy to obtain, and does not compete with humans. Water hyacinth has a fairly high content of protein, fiber, fat, and energy. The purpose of this study was to analyze the effect of the use of water hyacinth-based forage rations on the performance of sorghum. The study was conducted experimentally using a completely randomized design (CRD). A total of 80 male mutton were placed in 20 cage plots, so that each cage plot consisted of 4 birds. The types of treatment used were P0 (100% rice bran) as control, P1 (75% rice bran + 25% water hyacinth), P2 (50% rice bran + 50% water hyacinth), P3 (25% rice bran + 75% water hyacinth). The variables observed were ration consumption, body weight gain, ration conversion, feed cost per gain, and mortality. The research data were analyzed using analysis of variance and if they showed significant differences, they were further tested using Duncan's multiple distance test. The results showed that the ration consumption, body weight gain, ration conversion, and feed cost per gain with the addition of water hyacinth in the ration statistically showed a significant difference while the mortality calculated descriptively did not show any difference. Mortality occurred in treatment P3 (25% rice bran + 75% water hyacinth). It can be concluded that in order to improve the performance of male gibbons, the provision of forage water hyacinth in the ration should not be more than 50%.